2020
DOI: 10.1177/0731948720929006
|View full text |Cite
|
Sign up to set email alerts
|

Executive Function and Planning Features of Students With Different Types of Learning Difficulties in Chinese Junior Middle School

Abstract: The aim of the present study was to investigate the executive function and planning features of students with different types of learning difficulties. Students with mathematics difficulty (MD; n = 17), reading difficulty (RD; n = 12), their commonalities (MDRD; n = 22), and their typically academically developing peers (TD; n = 22) were evaluated on an array of cognitive measures (working memory, inhibition, and planning) individually. Results revealed significant differences among groups on various cognitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 53 publications
1
10
0
1
Order By: Relevance
“…Students with RDs experienced updating deficits, whereas students with RDMDs suffered from extensive executive function deficits in shifting, inhibition, and updating. These findings were consistent with previous studies that have indicated impaired executive functioning in students with RDMDs ( Sluis et al, 2004 ; Wang et al, 2008b ; Peng et al, 2013 ; Zhang et al, 2016 ; Deng et al, 2018 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Students with RDs experienced updating deficits, whereas students with RDMDs suffered from extensive executive function deficits in shifting, inhibition, and updating. These findings were consistent with previous studies that have indicated impaired executive functioning in students with RDMDs ( Sluis et al, 2004 ; Wang et al, 2008b ; Peng et al, 2013 ; Zhang et al, 2016 ; Deng et al, 2018 ).…”
Section: Discussionsupporting
confidence: 93%
“…Compared to typical students, RD students performed worse in the inhibitory control and attention switching tasks ( Hari and Renvall, 2001 ; Leong et al, 2007 ). Students with comorbid disabilities were generally deficient in WM updating, inhibition, and shifting of executive function ( Sluis et al, 2004 ; Wang et al, 2008a ; Peng et al, 2013 ; Zhang et al, 2016 ; Deng et al, 2018 ). Based on previous findings, it was found that different types of LDs may have heterogeneous cognitive defects heterogeneity ( Andersson, 2010 ; Peng and Fuchs, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Peng et al (2013) also found that Chinese children with reading difficulties at age 11 exhibited deficits in working memory, inhibition control, and rapid naming. Similarly, Deng et al (2020) showed that Chinese children with reading difficulties aged 12-15 performed poorly in inhibition control. None of these studies have examined the EF skills of working memory and inhibition control with L1 and L2 language skills together as correlates of Chinese and English word reading difficulty in a longitudinal study, so the interacting roles of each of these skills lack rigorous study especially for poor readers.…”
Section: Executive Functioning and Reading Difficultiesmentioning
confidence: 98%
“…48 children (25 boys and 23 girls; aged 5.87) whose word reading scores fell into the bottom 25% of all children in our sample were identified as poor readers. The cut‐off value of 25% was chosen because it was commonly used to identify poor readers in previous research (Darney, Reinke, Herman, Stormont, & Ialongo, 2013; Deng, Cai, Zhou, & Leung, 2020; Limbrick, Wheldall, & Madelaine, 2012; Liu et al, 2010; McBride‐Chang et al, 2013). And among the remaining children in the sample ( n = 142), 48 children (25 boys and 23 girls; aged 5.89) were selected as the normal readers by a matching procedure.…”
Section: Methodsmentioning
confidence: 99%